2015
DOI: 10.1016/j.drugalcdep.2015.07.432
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia level and response to computer-based training in cognitive behavioral therapy among cocaine-dependent methadone-maintained individuals

Abstract: Background-Alexithymia, a characteristic marked by poor ability to identify, define and communicate emotions, has been associated with poorer treatment outcome, including traditional clinician delivered CBT. Computerized cognitive behavioral therapy (CBT4CBT), an effective adjunct to treatment, may provide a means of conveying skills without requiring interaction with a clinician.Methods-Seventy-three methadone maintained, cocaine dependent individuals participating in an 8-week randomized clinical trial compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Other empirical research shows no connection between alexithymia and abstinence, length of treatment, and adherence to treatment. (De Haan et al, 2011 ;Morie, Nich, Hunkele, Potenza, & Carroll, 2015). The absence of correlation can be attributed to the fact that dropout and recurrence of substance use depend on numerous factors rather than a single element.…”
Section: Discussionmentioning
confidence: 99%
“…Other empirical research shows no connection between alexithymia and abstinence, length of treatment, and adherence to treatment. (De Haan et al, 2011 ;Morie, Nich, Hunkele, Potenza, & Carroll, 2015). The absence of correlation can be attributed to the fact that dropout and recurrence of substance use depend on numerous factors rather than a single element.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such individuals may seek to relieve depression or anxiety brought about by alexithymia by consuming alcohol or other drugs [16]. However, alexithymia may represent a separate entity, [17] consistent with observations that not all individuals with co-occurring alexithymia and substance dependence exhibit affective disorders [18]. Reports on alexithymia have shown a link between alexithymia and a chronically elevated stress response [19], perhaps because an inability to identify negative emotion makes such emotions harder to regulate.…”
mentioning
confidence: 80%
“…A prospective study on subjects with alcohol dependence by Junghanns et al [32] in 2005 found that alexithymia scores were not associated with the risk of relapse at 6-week follow-up [32]. A recent research confirmed that alexithymia was not associated with treatment adherence or retention in an 8-week randomized clinical trial by Morie et al [18] in 2015 [18]. Thus, evidence on the relationship between alexithymia and treatment outcome is limited and non-univocal.…”
Section: Issn: 2578-0042mentioning
confidence: 99%